Sound methods for the synthesis of nanoparticles from biological molecules. Issue 17 (23rd July 2021) - Bhangu, Sukhvir Kaur; Baral, Anshul; Zhu, Haiyan; Ashokkumar, Muthupandian; Cavalieri, Francesca
Abstract : Low and high frequency ultrasonic techniques offer a green strategy to synthesize multifunctional nanoparticles from small aromatic biological molecules and proteins with tunable size, morphology, and optical and bio-functional properties. Abstract : The development of simple, green, reproducible, and scalable approaches for synthesizing nanoparticles from biomolecules is important to advance nanomaterials towards therapeutic applications. Microreactors generated by high frequency ultrasound provide a one pot-platform to alter the physiochemical properties and stability of various types of biomolecules to ultimately generate multifunctional nanoparticles with controlled size and morphology. Herein, recent advancements in the field of nanoparticles fabrication from amino acids, phenolics, peptides and proteins using both high and low frequency ultrasound are reviewed. In particular, the sound driven self-assembly of biomolecules into nanoparticles by using high frequency ultrasound, as an emerging and innovative approach, is discussed in detail.